OPERASI PENANGKAPAN IKAN DI PERAIRAN KABUPATEN NIAS - Polem, Muhammad Iqbal; Faisal Syahputra; Agus Naufal (Lembaga Riset dan Inovasi Kreyat Center, 2025)
Nias Regency is one of the areas of North Sumatra Province located in the North Sumatra region and is located on an island called Nias Island. Nias Regency is located to the west of Sumatra Island and is surrounded by the Indian Ocean. This study aims to examine the composition of the catch and the challenges faced by fishermen based on the fishing operation area in the waters of Nias Regency. This study uses a descriptive quantitative research method. Data collection includes primary data and secondary data collected through observation, interviews and documentation. 294 people who were sampled in this study represented each sub-district based on the TPI. The results of the study showed that gray tuna was the main catch in fishing operations, with a total catch of (71%), large barracuda fish reached a total catch of (21%), while by-catch such as grouper, kurisi, and snapper amounted to (8%). The natural migration pattern that passes through Nias waters can cause the spread of this fish, especially in February and March. The main challenges or obstacles faced by fishermen in Nias Regency are generally every February-March season which has high rainfall, fluctuations in fish prices, and inadequate facilities. This makes it difficult for fishermen to carry out fishing activities.